INTEGRATED MARKETING COMMUNICATION (IMC) DIVISI EVENT DAN BANQUET POSE IN HOTEL SOLO: INTEGRATED MARKETING COMMUNICATION (IMC) DIVISI EVENT DAN BANQUET POSE IN HOTEL SOLO - Ikhsan Saputro, Muhammad; Sekar Wangi, Maya; Maria H, Dewi (Solidaritas, 2025)
This study aims to analyze the Integrated Marketing Communication (IMC) strategiesimplemented by the Event and Banquet Division at Pose In Hotel Solo to enhancecompetitiveness and attract customers. This research applies a qualitative descriptive approachthrough in-depth interviews, direct observation, and documentation. The results indicate thatIMC strategies, such as digital advertising, public relations, personal selling, direct marketing,and sales promotion, have effectively increased brand awareness and customer loyalty.However, limitations in human resources, particularly in CSR activities, remain a challenge.Despite this, the IMC approach enabled Pose In Hotel Solo to stay competitive with only asingle marketing division. This study recommends strengthening strategic and innovative IMCplanning to improve performance.Keywords: Integrated Marketing Communication, Event, Banquet, Hotel, Marketing Strategy